The Role of Hypocalcemia in Preeclampsia: A Review on Calcium Supplementation in Pregnancy - Dimas Kirana Mahaputra (PT Dexa Medica, 2025)
Preeclampsia is a hypertensive disorder that contributes to the high maternal death rate worldwide. Furthermore, preeclampsia adversely affects fetal development due to reduced placental blood flow. Numerous factors are known to affect the development and pathophysiology of preeclampsia, one of them is micronutrient deficiency. Calcium, an essential mineral, plays a crucial role in the mechanism of vascular smooth muscle contraction, which regulates vascular tone and blood pressure. Placental dysfunction, a hallmark of preeclampsia, leads to hypocalcemia, which, in turn, exacerbates the condition through compensatory mechanisms involving parathyroid hormone. Conversely, adequate calcium intake has been proven beneficial and is recommended during pregnancy. This article aims to review current guidelines on calcium supplementation and nutritional recommendations as a viable strategy to minimize the risk of preeclampsia.